Do inflation expectations matter for small, open economies? Empirical evidence from the Solomon Islands - Angeline B. Rohoia; Parmendra Sharma (Journal of Risk and Financial Management, 2021)
This paper examines the role of inflation expectations in Solomon Islands, a Pacific Island Country, using the Hybrid New Keynesian Phillips Curve model. The study applies the Generalized Method of Moments to estimate the Hybrid New Keynesian Philips Curve model using quarterly time series data for the period 2003-2017. The study confirms the existence of a Hybrid New Keynesian Philips Curve for Solomon Islands and finds that both backward-looking and forward-looking processes matter for inflation. Fuel prices and output gap are important indicators of current inflation. The study highlights key areas to further investigate including the weak monetary transmission mechanism and to examine the exchange rate pass through effect onto domestic prices. Studies on the role of inflation expectations in small, open, economies of the Pacific, such as Solomon Islands, is limited. This paper fills this void in literature by using quarterly time-series data to build a Hybrid New Keynesian Philips Curve model for Solomon Islands.
Keywords: E12; E31; E50; E60; 330; inflation; Phillips Curve; Solomon Islands